2011
DOI: 10.1016/j.chemgeo.2010.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A stable (Li, O) and radiogenic (Sr, Nd) isotope perspective on metasomatic processes in a subducting slab

Abstract: Two distinct types of eclogites from the Raspas Complex (Ecuador), which can be distinguished based on petrography and trace element geochemistry, were analyzed for their stable (Li, O) and radiogenic (Sr, Nd) isotope signature to constrain metasomatic changes due to fluid-overprinting in metabasaltic rocks at high-pressure conditions and to identify fluid sources. MORB-type eclogites are characterized by a relative LREE depletion similar to MORB. High-pressure (HP) minerals from this type of eclogite have hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 108 publications
1
42
0
Order By: Relevance
“…Therefore, elevated  18 O values may be related to inherited effects of low-temperature seawater alteration from the precursor rock, or to the metasomatic fluid itself (Putlitz et al, 2000;Halama et al, 2011). Both possibilities will be discussed in turn.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, elevated  18 O values may be related to inherited effects of low-temperature seawater alteration from the precursor rock, or to the metasomatic fluid itself (Putlitz et al, 2000;Halama et al, 2011). Both possibilities will be discussed in turn.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…It has also been demonstrated that fluids in HP metamorphic rocks play a key role in promoting equilibration of isotopic systems used as geochronometers (Glodny et al, 2003(Glodny et al, , 2008. In turn, some isotopic systems may still record the effects of previous seafloor alteration or the isotopic signature of the precursor rock (Halama et al, 2010(Halama et al, , 2011John et al, 2011;Miller et al, 1988;Putlitz et al, 2000).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations